Pengaruh Profitabilitas, Leverage, dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Sandra Kornelis; Suyanto Suyanto; Kusuma Chandra Kirana (Yayasan Literasi Ilmiah Indonesia, 2025)
Purpose: This study aims ti determine: (1) To prove whether the effect of profitability on firm value in manufacturing companies listed on the Indonesia Stock Exchange, (2) To prove whether the effect of leverage on firm value in manufacturing companies listed on the Indonesia Stock Exchange, (3) To prove whether the effect of company size on firm value in manufacturing companies listed on the Indonesia Stock Exchange Method: This type of research is quantitative researchusing the document method. Sampel were taken using purposive sampling technique. The sample consisted of 300 data from 60 companies listed on the Indonesia Stock Exchange 2019-2023. The data analysis technique used is quantitative analysis using Eviews Finding: Based on the research result, it show that Profitability has a positive effect on firm value, Leverage has a positive effect on firm value, company size has a negative effect on firm value. Novelty: This study adds the leverage variable as a factor affecting firm value, which has not been studied in previous studies.